2004
DOI: 10.1002/bit.20288
|View full text |Cite
|
Sign up to set email alerts
|

Increased megakaryopoiesis in cultures of CD34‐enriched cord blood cells maintained at 39°C

Abstract: Based on previous evidence suggesting positive effects of fever on in vivo hematopoiesis, we tested the effect of hyperthermia on megakaryopoiesis (MK) in ex vivo cultures of CD34-enriched cord blood (CB) cells. The cells were cultured at 37jC or 39jC for 14 days in cytokine conditions optimized for megakaryocyte development and analyzed periodically. Compared to 37jC, the cultures maintained at 39jC produced significantly more (up to 10-fold) total cells, myeloid and MK progenitors, and total MKs, and showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…GM6001 was added at day 12 following preliminary experiments showing no beneficial effect on GPIba expression when added at earlier time (data not shown). Cultures were maintained in a humidified atmosphere (10% CO 2 , 20% O 2 ) at 398C and 378C for the first and last 7 days of culture, respectively, to increase Mk and PLP yields [9,18]. Viable nucleated cells were manually counted as described [7].…”
Section: Production Of Plps From Human Cb Cd34þ Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…GM6001 was added at day 12 following preliminary experiments showing no beneficial effect on GPIba expression when added at earlier time (data not shown). Cultures were maintained in a humidified atmosphere (10% CO 2 , 20% O 2 ) at 398C and 378C for the first and last 7 days of culture, respectively, to increase Mk and PLP yields [9,18]. Viable nucleated cells were manually counted as described [7].…”
Section: Production Of Plps From Human Cb Cd34þ Cellsmentioning
confidence: 99%
“…Megakaryocyte (Mk) and platelet production have been described from different sources of cells such as cell lines [1], embryonic stem cell [2,3], and hematopoietic stem cells [4][5][6][7][8] maintained in suspension cultures [4,5,7,9], or with feeder layers [2,3,6] or in bioreactors [8] (recently reviewed in [10]). Despite many efforts, platelet-like particles' (PLP) yield remains the Achilles' heel of all protocols described to date.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the strong impact on erythropoiesis reported herein is a direct consequence of MH. Consistent with this, several investigations have shown that the temperature of incubation can impact the growth and differentiation of primary bone marrow cells [20,[33][34][35].…”
Section: Discussionmentioning
confidence: 78%
“…In line with the impact of WBH on platelet levels, we previously demonstrated that expansion and differentiation of cord blood (CB) CD34 + cells along the megakaryocytic (MK) lineage were significantly increased under MH (ie, 39°C) [20]. MH-mediated acceleration of MK differentiation and maturation was shown to be rapid [21], associated with increased levels of the heat shock protein HSP70 [20] and of several transcription factors implicated in erythroid and megakaryocyte differentiation [21].…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation